Childcare and maternal part-time employment: A natural experiment using Swiss cantons - Laura Ravazzini (Swiss Journal of Economics and Statistics, 2018)
Fuelled by federal stimuli of 440 million Swiss francs, the staggered expansion of childcare in many cantons allows the evaluation of this family policy on female labour supply. With new cantonal data, this study analyses both the decision to participate in the labour market and the intensity of participation. Empirical results of difference-in-differences regressions show that mothers work at higher percentage rates if they live in cantons that have expanded their childcare services more than the national average. The reform stimulated part-time employment of between 20 and 36 h per week by 2 percentage points. The expansion of childcare particularly affected women with two children and upper-secondary education, who are married or cohabit with their partner.
Keywords: J13; J22; H40; 330; Childcare places; Maternal employment; Policy evaluation; Quasi-natural experiment; Part-time